Implementación de un modelo teórico para la remoción de ácido láctico mediante adsorbentes sólidos (2018)
In this work, the adsorption behavior of lactic acid when it is in aqueous solution was studied by means of the Langmuir and Freundlich isotherm models. The adsorption behavior of lactic acid when it is in a ternary mixture with formic and acetic acid was studied through the IAST model (ideal adsorbed solution theory), executed in the Matlab® program. In this work the solid adsorbent was selected under the criteria of selectivity and capacity, using sufficient data from the literature and the ideal theory of the IAST adsorption solution (Ideal Adsorption Solution Theory) and making a coupling Aspen Propierties®- Excel®-Matlab ®, where it could be established that the coupling works correctly to study the adsorption behavior of carboxylic acids in solid adsorbents, being the adsorbent Amberlite IRA-67 the adsorbent that has a favorable behavior for the adsorption of lactic acid.